O incômodo em relação ao ruído urbano em taxistas do município de São Paulo-SP - Grüdtner, Marjorie Juliana Silva (2015)
Continuous noise exposure can cause hearing effects and non-hearing. The annoyance is the one of the most important effect of noise exposure. The annoyance of exposure of noise can cause several negative responses such as anxiety, restlessness, disappointment, depression, distraction, exhaustion, dissatisfaction, anger. Purpose: To evaluate the annoyance and the others complaints by noise among taxi drivers in the city of São Paulo-SP. Method: The sample size was 153 taxi drivers. Auditory and non auditory noise effects was conducted through a questionnaire adapted, based on Ferreira (2013). Statistical analysis was performed using the chi-square test to assess the association between the study variables and four outcomes (annoyance, stress, communication disorders and hearing loss). Cronbach s Alpha Test was used to analyze the questionnaire reliability. Results: Most taxi drivers (73.86%) makes no mention of quiet or tranquility as their place of work and 83% consider the noise of moderate to intense. 58.48% think that adds to the existing noise. The main sources of noise outside the vehicle taxi drivers were cited by the vehicle traffic, construction and trade. The adverse effects of noise, the most observed were: stress, discomfort, difficulty communicating and understanding what others say, moodiness, irritability, fatigue and tinnitus. 60% of taxi drivers think the noise can harm them in some way, and the stress (11.11%) and hearing loss (9.15%) were the most cited. To decrease the 43.14% noise suggested education and awareness of individuals. Regarding the hearing, only 32.68% think that hears the same way he heard before. Significant associations were found with the four outcomes with the following variables: the lack of attention, dizziness, moodiness, annoyance, pressure rise, tinnitus, fatigue, lack of appetite, interference with work efficiency and implementation tasks. As for the first three outcomes (annoyance, stress and communication difficulties) the variable with significance was the hearing of the change in self-perception. Variables: irritation, work efficiency, uncomfortable with loud sounds, inattention, understand what others say appeared related only to stress outcomes and difficulty communicating with others. Conclusion: annoyance, stress, difficulty communicating and self-perception of hearing loss were statistically associated with urban noise and several adverse health effects resulting from this exposure. The internal consistency (reliability) of the questionnaire used in the survey was excellent